Excitation and Active Control of Propagating Surface Plasmon Polaritons in Graphene - Gao, Weilu; Shi, Gang; Jin, Zehua; Shu, Jie; Zhang, Qi; Vajtai, Robert; Ajayan, Pulickel M; Kono, Junichiro; Xu, Qianfan (Nano letters, 2013)
We demonstrate the excitation and gate control of highly confined surface plasmon polaritons propagating through monolayer graphene using a silicon diffractive grating. The normal-incidence infrared transmission spectra exhibit pronounced dips due to guided-wave resonances, whose frequencies can be tuned over a range of ∼80 cm–1 by applying a gate voltage. This novel structure provides a way to excite and actively control plasmonic waves in graphene and is thus an important building block of graphene plasmonic systems.